Adalimumab (TNFα Inhibitor) Therapy Exacerbates IgA Glomerulonephritis Acute Renal Injury and Induces Lupus Autoantibodies in a Psoriasis Patient - S. S. Wei; R. Sinniah (Case Reports in Nephrology)
Adalimumab (Humira) is a tumour necrosis factor α (TNFα) inhibitor that is approved for the treatment of rheumatoid arthritis, psoriasis, psoriatic arthritis, Crohn's disease, ankylosing spondylitis, and juvenile idiopathic arthritis (Sullivan and Preda (2009), Klinkhoff (2004), and Medicare Australia). Use of TNFα inhibitors is associated with the induction of autoimmunity (systemic lupus erythematosus, vasculitis, and sarcoidosis or sarcoid-like granulomas) (Ramos-Casals et al. (2010)). We report a patient with extensive psoriasis presenting with renal failure and seropositive lupus markers without classical lupus nephritis after 18 months treatment with adalimumab. He has renal biopsy proven IgA nephritis instead. Renal biopsy is the key diagnostic tool in patients presenting with adalimumab induced nephritis and renal failure. He made a remarkable recovery after adalimumab cessation and steroid treatment. To our knowledge, this is a unique case of a psoriasis patient presenting with seropositive lupus markers without classical lupus nephritis renal failure and had renal biopsy proven IgA glomerulonephritis after receiving adalimumab.